Workshop Menulis Dongeng Berbasis Augmented Reality untuk Meningkatkan Keterampilan Literasi Digital Guru SD - Wulan Tri Puji Utami; Novy Trisnani; Syauqie Muhammad Marier (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2023)
The location of SD N Tukharjo, which is about 30 km from the Kulon Progo district center, makes educational facilities such as the regional library difficult to reach for students and teachers. The mobile library car run by the Kulonprogo regional library has also not reached SD N Tukharjo. The impact is that students and teachers only use the school library as literacy material. Currently Face-to-Face Learning (PTM) also limits the circulation of borrowed books in the school library. Through this activity, teachers will be given a deeper understanding of the nature of the literacy-numeration school program. Teachers are also encouraged to produce works in the form of fairy tale books that can add to reading material in reading corners or libraries, as well as increase skills regarding digital literacy by making literacy books based on augmented reality (AR). This service activity is carried out through four stages, namely planning, implementation, mentoring, and evaluation and reflection. From the results of the evaluation and reflection activities it can be concluded: 1) there is an increase in knowledge and digital literacy skills for teachers at SD Negeri Tukharjo, and 2) teachers at SD Negeri Tukharjo have succeeded in composing augmented reality fairy tales and have been ISBN-approved.